Sunk Investments Lead to Unpredictable Prices - Mailath, George J; Postlewaite, Andrew; Samuelson, Larry (American Economic Review, 2004)
We study transactions that require investments before trading in a competitive market, when forward contracts fixing the transaction price are absent. We show that, despite the market being perfectly competitive and subject to arbitrarily little uncertainty, the inability to jointly determine investment levels and prices may make it impossible for buyers and sellers to predict the prices at which they will trade, leading to inefficient levels of investment and trade.